KEWENANGAN PEMERINTAH PROVINSI BALI DALAM PENYELENGGARAAN PENANAMAN MODAL BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Anak Agung Ngurah Agung Satrya Diana (University of Udayana, 2015)
Licensing is one of the fundamental problems in the administration of the licensing applicant investment in Indonesia . Licensing is one of the very important first step in starting a business activity which is a testament to the legality of an otherwise legitimate business activities or the permissibility of a person or legal entity to conduct business activities . With the enactment of Law No. 25 of 2007 on Investment has shown that the character of a paradigmatic shift in the organization of centralized to decentralized investment in Indonesia , with the authority given to the Government of Blood to organize affairs in the administration of Investment mandatory . Especially with the issuance of Presidential Decree No. 27 Year 2009 on One Stop Services in the Field of Investment , is expected to provide legal certainty to investors who want to invest in an area designated by the legislation in force . The Province of Bali has established Investment and Licensing Agency Bali Province as Provincial Tool to Investment ( PDPPM ) , which has been granted delegation of authority from the Governor of Bali to host Investment in accordance with the authority granted by the laws and existing undnagan . However, there are shortcomings in the regulation of the Governor of Bali Delegation Authority in the Field Licensing and Nonperizinan To the Head of Investment and Licensing province of Bali , which does not include the authority to issue permissions to Investment based on legislation in the field of investment , so that in case PDPPM this as an institution in Bali province can not provide legal certainty associated with the licensing application filed by investors in doing business in Bali Province in accordance with the issuance authority.